Location-based Mobile Application for Blood Donor Search - Iparraguirre-Villanueva, Orlando (2022)
Technological advances and the massive use of mobile devices have led to the exponential evolution of mobile applications in the health sector. Blood donation centers frequently suffer blood shortages due to lack of donations, which is why blood donation requests are frequently seen on social networks for blood donors in urgent need of a transfusion of a specific blood group. Mobile applications for blood donation are crucial in the health sector, since it allows donors and blood donation centers to communicate immediately to coordinate with each other, minimizing the time to perform the donation process. The present work was to develop a location-based mobile application for the search of blood donors, with the objective of increasing the number of donors, having a greater population reach, and reducing the time to search for blood donors. The results obtained show a significant increase of 39.58% in the number of donors, a reduction of 53.2% in the search time, and a greater population reach.